Assessment in music therapy: strategies and applications to clinical practice in an international perspective. Issue 1 (1st June 2016) - Vianna, Shirlene; Gattino, Gustavo; Ferrari, Karina; Alcântara-Silva, Tereza; Araujo, Gustavo; Rodrigues, Igor
Abstract : Background : In music therapy field, assessment is aimed at understanding the client's unique strengths and challenges determining whether the client may benefit from music therapy treatment. There are different perspectives to conduct this phase in music therapy process according to the use of distinct scales, questionnaires and musical experiences. Objective : Drawing from the experience of music therapists in three different countries (Argentina, Brazil and United States) this roundtable reflects upon and connects perspectives on how to implement distinct assessments in music therapy clinical practice. Content : The members of the roundtable reflect upon their experience as clinicians using assessments in different areas of clinical practice. Themes explored include strategies and applications of some music therapy assessments: Individual Music Therapy Assessment Profile (IMTAP), Intramusical Relationship Scale (IRS) and Individual Music-Centered Assessment Profile for Neurodevelopmental Disorders (IMCAP-ND). Moreover, they are presented with some considerations on how to bond assessments from others disciplines (psychology and neuropsychology) in music therapy practice.